Phonological Interference in Medical English Pronunciation: An Analysis of Pronunciation Errors Among Nursing Students - Finny Widya Fransiska; Bastian Sugandi (Universitas Muhammadiyah Lampung, 2025)
This study aimed to analyze the types of English pronunciation errors made by Nursing students and to identify the factors contributing to these errors in the context of English for Nursing instruction. A qualitative descriptive research design was employed, involving 18 fourth-semester Nursing students at Universitas Muhammadiyah Pringsewu, Indonesia, who were selected through purposive sampling. Data were collected through a pronunciation test consisting of medical and nursing-related terminology and semi-structured interviews. All pronunciation performances were audio-recorded and analyzed phonologically, while interview data were examined thematically. The findings revealed that Nursing students experienced systematic pronunciation errors, particularly related to silent letters, consonant clusters, vowel reduction, and incorrect word stress in multisyllabic medical terms. Errors were predominantly influenced by first-language phonological interference, limited exposure to spoken medical English, and instructional practices that emphasized reading comprehension rather than oral and pronunciation-focused activities. These pronunciation difficulties have the potential to affect intelligibility and professional communication in clinical settings. In conclusion, the study highlights the need for pronunciation-focused instruction that is contextualized within authentic clinical communication. It is recommended that English for Nursing courses integrate more listening activities, clinical simulations, and explicit pronunciation training. Future research is suggested to involve larger samples and to examine the effectiveness of instructional interventions designed to improve pronunciation accuracy and clinical communication skills among Nursing students.